DILEMA KEBERAGAMAAN MUSLIM PENGIKUT SAPTA DARMA DALAM MENEMUKAN NILAI-NILAI SPIRITUALITAS - Wiwik Setiyani Khasbullah (UIN Sunan Kalijaga Yogyakarta, 2020)
Adherents of Islam and sapta darma feel their beliefs have been inherent in their hearts and minds. Spiritual values are felt and have an impact on changing behavior for the better. This article wants to explain the adherents of religions who experience religious dilemmas in Islam and Sapta Darma in Surabaya. The in-depth interview method is used to find the level of religious maturity from the aspects of sharia and the application of religious teachings. Research findings on spiritual values or religious experience are felt in sapta darma but do not want to leave Islam. This means that spirituality has a higher value than religion. Islam remains as its identity, however, sapta darma becomes its belief or path.